The Effect Of Managerial Coaching, Person-Job Fit, And Motivation Toward Employee Performance: The Mediating Role Of Satisfaction And Engagement - Krisna Wahyu Nugraha; Eka Nurlita Kurnia Wardhani (Owner : Riset dan Jurnal Akuntansi, 2022)
This study examines the effect of managerial coaching, person-job fit, and motivation toward employee performance with the mediating role of employee satisfaction and engagement based on a study on a manufacturing enterprise in Indonesia listed on the Indonesia Stock Exchange (IDX). This research uses a quantitative approach with 116 respondents from manufacturing companies listed on the Indonesia Stock Exchange (IDX) in Indonesia. The results of this study are (1) there is a positive and significant relationship between managerial coaching and performance, (2) there is no relationship between person-job fit and performance, (3) there is no influence on motivation to performance, (4) there is no effect of managerial coaching on satisfaction, (5) there is a positive and significant relationship between person-job fit and satisfaction, (6) there is a positive and significant relationship between motivation and satisfaction, (7) there is a positive and significant relationship between managerial coaching and engagement, (8) there is no relationship between person-job fit and engagement, (9) there is a positive and significant relationship between motivation and engagement, (10) there is no relationship between satisfaction and performance, and (11) there is a positive and significant relationship between engagement and performance.